Morphology and molecular phylogeny of Macrobrachium prachuapense sp. nov. (Decapoda: Palaemonidae) from Southern Thailand - Saengphan, Nukul; Panijpan, Bhinyo; Senapin, Saengchan; Laosinchai, Parames; Suksomnit, Auaree; Phiwsaiya, Kornsunee (Zootaxa, 2021)
A new species of small freshwater prawn in the Macrobrachium pilimanus species group was found in the upper southern peninsula of Thailand. The prawns in this group exhibit velvet setae on the telopodites of the second pereiopods. The new species, named M. prachuapense sp. nov., is endemic to Thailand. It has several characteristics that make it standing apart and different from closely related species in the group, e.g. M. naiyanetri, M. forcipatum, M. malayanum, M. dienbienphuense, M. eriocheirum, and M. pilosum. The distinguishing characteristic of the new species is the shape of carpus of the second pereiopod (sub-cylindrical and subequal to palm), similar only to that of M. dienbienphuense. However, a fully-grown male of the new species was less than two-third the size of a fully-grown male M. dienbienphuense. Phylogenetic analysis further enhanced its novel species status with respect to its position in the phylogenetic tree relative to other closely related species.